The phenomenon of stability of the average value of electrocutaneous conductivity in “points- sources of the meridians” - Strakhova, Oksana; Ryzhov, Alexey; Страхова, Оксана Петрівна; Рижов, Олексій Анатолійович (Praha, Czech Republic, 2017)
It is the attempt to improve the quality of electro-acupuncture diagnostics. For this purpose, a study involving 210 volunteers, over three years, in different seasons was provided. Definition the statistically homogeneous data as an array comprising the measuring of electrocutaneous characteristics in every separate "point - source" and the visualization the results obtained in this way, make possible to observe the stability of the average values of the "point - source" data. It also makes possible to assume the permissible range of normal and abnormal values of electrodermal characteristics.
Keywords: electrodermal characteristics; visualization; statistic processing